The role of the nurse in pediatric hemodialysis (Research, Society and Development, 2022)
Objective: To describe the care provided by nurses to children during hemodialysis sessions. Methodology: This is a literature review with a qualitative approach. Eight articles available in the LILACS, MEDLINE and BDENF databases, written in Portuguese and published from 2010 to 2021, were used. To analyze the selected articles, two tables were created: Table 1 with the number, title, author, year, journal and database, and Table 2, which shows the number, title, objective and main results. Results: Of the articles found, few address children, which demonstrates that studies related to the topic are still very limited, justifying the small number of articles that made up the final sample. The prevalence of the following themes was observed: quality of life and nursing care for patients on hemodialysis. In general, studies show that nurses need to have great knowledge, sensitivity and humanization, to know how to deal with so many technologies and the administrative part, without putting the care provided to the child in the background. Conclusion: It is concluded that the nurse cannot be just a performer of technical care to the patient, he/she needs to provide a treatment that is less traumatic, minimizing the suffering caused to the child due to their illness and treatment. Through this study, the importance of future studies in the field of nursing in pediatric nephrology was evidenced, especially with regard to the care provided to children in hemodialysis treatment, from the moment of admission to discharge.